Multicenter Phase II Trial of the WEE1 Inhibitor Adavosertib in Refractory Solid Tumors Harboring CCNE1 Amplification. Issue 9 (20th March 2023) - Fu, Siqing; Yao, Shuyang; Yuan, Yuan; Previs, Rebecca A.; Elias, Anthony D.; Carvajal, Richard D.; George, Thomas J.; Yuan, Ying; Yu, Lihou; Westin, Shannon N.; Xing, Yan; Dumbrava, Ecaterina E.; et al.
Abstract : PURPOSE: Preclinical cancer models harboring CCNE1 amplification were more sensitive to adavosertib treatment, a WEE1 kinase inhibitor, than models without amplification. Thus, we conducted this phase II study to assess the antitumor activity of adavosertib in patients with CCNE1 -amplified, advanced refractory solid tumors. PATIENTS AND METHODS: Patients aged ≥ 18 years with measurable disease and refractory solid tumors harboring CCNE1 amplification, an Eastern Cooperative Oncology Group performance status of 0-1, and adequate organ function were studied. Patients received 300 mg of adavosertib once daily on days 1 through 5 and 8 through 12 of a 21-day cycle. The trial followed Bayesian optimal phase II design. The primary end point was objective response rate (ORR). RESULTS: Thirty patients were enrolled. The median follow-up duration was 9.9 months. Eight patients had partial responses (PRs), and three had stable disease (SD) ≥ 6 months, with an ORR of 27% (95% CI, 12 to 46), a SD ≥ 6 months/PR rate of 37% (95% CI, 20 to 56), a median progression-free survival duration of 4.1 months (95% CI, 1.8 to 6.4), and a median overall survival duration of 9.9 months (95% CI, 4.8 to 15). Fourteen patients with epithelial ovarian cancer showed an ORR of 36% (95% CI, 13 to 65) and SD ≥ 6 months/PR of 57% (95% CI, 29 to 82), a median progression-free survival duration of 6.3 months (95% CI, 2.4 to 10.2), and a median overall survival duration of 14.9 months (95% CI, 8.9 to 20.9). Common treatment-related toxicities were GI, hematologic toxicities, and fatigue. CONCLUSION: Adavosertib monotherapy demonstrates a manageable toxicity profile and promising clinical activity in refractory solid tumors harboring CCNE1 amplification, especially in epithelial ovarian cancer. Further study of adavosertib, alone or in combination with other therapeutic agents, in CCNE1 -amplified epithelial ovarian cancer is warranted.